Mandibular Canine Index as A Tool in Gender Identification - A Study in Malwa Population (Indian Journal of Forensic Medicine & Toxicology, 2020)
Teeth are the hardest tissue in the body. Mandibular canines are important tooth in the human body whichshows significant sexual dimorphism. Mandibular canine index can be used for gender identification duringmass disasters and crime scenes. The purpose of this study was to investigate the accuracy with which gendercan be differentiated in Malwa population by using the Mandibular Canine Index and sexual dimorphism.Materials and Method: The study sample includes 300 Mandibular casts of people residing in Malwa. Itincluded 137 males and 163 female participants. Mesio distal diameter of mandibular canines were measuredfrom mesial contact point to distal contact point of right and left mandibular canines. Inter canine distancewas measured between tips of both canines. These were used for deriving MCI and determining sexualdimorphism exhibited by mandibular canines.Results: The mesiodistal width of mandibular canine were larger in males than in females. The meandifference of MCI between males and females were more on the left canine, thus making it highly significant(P Value<0.001). The standard mandibular canine index for Malwa population was obtained as 0.262.Sexual dimorphism of right mandibular canine was estimated as 4.30% and for left mandibular canine was5.58%. Sexual dimorphism of mandibular canine is more on left side. The overall percentage accuracyof sex prediction using standard mandibular canine was found to be 65.52%. Conclusion: Tooth remainsobtained from crime scenes or disasters can be used for gender identification as this method is very simple,accurate and useful.